#216 Kinetic study of melatonin by validated stability indicating HPTLC method - Sutar, Shubhangi V; Patil, Sachinkumar V (Journal of Pharmaceutical Chemistry, 2022)
Chemical stability of pharmaceutical molecules is a matter of great concern as it affects the safety and efficacy of the drug product. Some degradation products and impurities may even have toxic effects. Therefore, it is very important to develop proper stability indicating method for Melatonin which possibly be used for stability testing and routine analysis. A rapid, sensitive with stability indicating HPTLC method be developed and validated to study degradation kinetics of Melatonin (MT) in alkaline, acidic and oxidative conditions. All degraded samples be chromatographed on Silica gel 60F 254 plates, developed using solvent system toluene: methanol: formic acid (7:3:0.1) and scanned at 290 nm.The developed method was validated as per ICH guidelines using validation parameters such as specificity, linearity and range, precision, accuracy, LOD and LOQ. Degradation kinetics of MT in acidic and alkaline medium was studied by degrading it underneath three distinct concentrations of alkali and acid at three different time interval. Degradation of melatonin into the alkaline and acidic medium was found to follow first order kinetics. Acid, alkaline and oxidative degradation reactions studied to determine the rates of the reaction and susceptibility of melatonin. The HPTLC technique established in this work is precise, specific, and accurate stability indicating statistical analysis proves the method is suitable for analysis of melatonin. Melatonin degraded in acidic, alkaline, oxidative stress conditions. Alkaline and acidic degradation of melatonin followed first order kinetics and higher degradation was found in 1N NaOH and 1N HCl.